ANALISIS YURIDIS TERHADAP PENERAPAN PERSIDANGAN PERKARA PIDANA SECARA ELEKTRONIK DALAM SITUASI PANDEMI COVID-19 - Abdul Mukti (2021)
The COVID-19 pandemic has caused changes in the order and pattern of human life by implementing a new normal life. One of those affected is the law enforcement sector in Indonesia. Criminal law enforcement ultimately implements making adjustments, especially when examining cases in court, namely by conducting virtual trials. This is a step to implement health protocols to maintain human safety. It's just that there is no regulation regarding this matter, where the Criminal Procedure Code only regulates by directly face-to-face method, so that the Supreme Court issues a Supreme Court Regulation (PERMA) to be the implementation of electronic remote trials (virtual). The problem raised in this study is how to apply the trial of criminal cases empirically during the COVID-19 pandemic as well as a Juridical review related to the virtual application courts based on PERMA in terms of the perspective of laws and regulations in Indonesia. This study uses a juridical empirical conceptual approach (conceptual approach) in the form of prevailing views and doctrines, statutory approach (statute approach), historical approach (historical approach), case approach (case approach), and comparative approach (comparative approach). The results of the study stated that the application of the virtual trial made a positive contribution to law enforcement in Indonesia, but still the implementation still has any problems. From the regulatory context, PERMA is a legal product that is binding and has legally force. It's just that this virtual trial arrangement needs to be leveled up to become a law so that it has parallels with the Criminal Procedure Code, or at least it can be proposed to the President to be issued as a Perppu. Keywords: covid-19 pandemic, electronic trial, laws and regulations